Changes in functional renal reserve as an early marker of renal dysfunction in patients with chronic obstructive pulmonary disease and essential hypertension - Akimova, L. S.; Акімова, Лілія Сергіївна (My University, 2025)
The aim of the study. To investigate changes in functional renal reserve (FRR) in patients with chronic obstructive pulmonary disease (COPD) stage II-III and essential hypertension (EH) stage II, to identify a correlation between the severity and stage of the underlying disease and the degree of reduced functional renal reserve (FRR).